CULTUROLOGICAL APPROACH IN TEACHING THE RUSSIAN LANGUAGE - Umarova Dilfuza Mamatkulovna (Journals Park Publishing, 2023)
The Russian language as a worldview subject is designed to ensure the unity and interaction of language, culture, personality in the process of learning and development of this personality. Some of the problems of “culturally appropriate” teaching of humanitarian subjects are already being solved in the course of students mastering different ways of mental and speech activity, gaining experience and skills of communicatively appropriate behavior, developing reflective consciousness, a culture of feelings, emotions, mental work, creating and maintaining a cultural environment in an educational institution, and last but not least, provided that the language is studied as a “code of culture”, and this is not only a special methodological, but also a general pedagogical task.
Keywords: memory, cultural background, traditions, customs, oral folk art, speech etiquette, sociocultural text, cultural competence.